2011
DOI: 10.1039/c0cc04999a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coadsorbent properties on the photovoltaic performance of dye-sensitized solar cells

Abstract: Stearic acid as a coadsorbent, which has a low dipole moment and high solubility, retarded the rate of dye adsorption during the competitive anchoring process on the TiO(2) layer in dye-sensitized solar cells (DSCs), thereby increasing the content of strongly bound dye on the TiO(2) surface. This resulted in an approximately 25% improvement in both J(SC) and the power conversion efficiency of the DSCs, even for much lower dye coverage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
85
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 15 publications
(24 reference statements)
3
85
0
Order By: Relevance
“…One of the reason for poor long-term stability of DSSCs is weakly bound dye molecules on TiO 2 surface12. Recently, the long-term stability of DSSCs has been improved through molecular engineering of a sensitizer in conjunction with the use of a nonvolatile electrolyte13141516.…”
mentioning
confidence: 99%
“…One of the reason for poor long-term stability of DSSCs is weakly bound dye molecules on TiO 2 surface12. Recently, the long-term stability of DSSCs has been improved through molecular engineering of a sensitizer in conjunction with the use of a nonvolatile electrolyte13141516.…”
mentioning
confidence: 99%
“…N719 was desorbed from the TiO 2 film by immersing the sensitized electrodes into 0.1 M KOH aqueous solutions. 30 The absorption intensity reached 14% at a concentration 10 times higher (3.0 mM).…”
Section: Dye and Coadsorbent Adsorption Behaviormentioning
confidence: 95%
“…Modification of the interface by the introduction of co-adsorbents along with the dye can alter the conduction band edge and shield the trap states of TiO 2 to influence the V oc , J sc , and the recombination reaction of the photo-induced electrons [58][59][60][61][62][63][64]. It was reported that stearic acid as a co-adsorbent, which has a low dipole moment and high solubility, hindered the rate of dye adsorption during the competitive anchoring process on the TiO 2 layer in DSC and increased the content of strongly bound dye on the TiO 2 surface [65]. This resulted in an approximately 25% improvement in J sc and the power conversion efficiency of the DSC even with much lower dye coverage.…”
Section: Tio 2 -Dye Junctionmentioning
confidence: 98%